The potential use of Alpinia galanga and Piper betle as growth promoters in the broiler industry: a review - Mohamed Kamil, Muhammad Ali Imran; Reduan, Mohd Farhan Hanif; Abu-Bakar, Luqman; Mohd Noor, Mohd Akmal; Shamsuddin, Shazana Hilda; Mohd Azmi, Amirul Faiz; Mahamud, Siti Nor Azizah (Chiang Mai University - Faculty of Veterinary Medicine, 2024)
Phytogenic feed additives (PFA) have been studied in many poultry researches primarily as growth promoters due to the growing interest in using natural products in farming. However, few researchers opted to study Piper betle (betel) and Alpinia galanga (greater galangal) as growth promoters in broilers despite these plants' abundance of beneficial phytoconstituents. Thus, this narrative review aims to provide insights to the readers on the characteristics and properties of P. betle and A. galanga to be used as growth promoters by supplementation to broiler chicken. Issues and knowledge addressed in this review article help poultry researchers and industry to explore the potential of P. betle and A. galanga to improve the performance of poultry flocks in the future.